Graph-theoretic concepts in computer science 37th International Workshop, WG 2011, Teplá Monastery, Czech Republic, June 21-24, 2011. Revised Papers - Kolman, Petr; Kratochvíl, Jan (Springer, 2011)
This book constitutes the revised selected papers of the 37th International Workshop on Graph-Theoretic Concepts in Computer Science, WG 2011, held at Teplá Monastery, Czech Republic, in June 2011. The 28 revised papers presented were carefully reviewed and selected from 52 submissions. The workshop aims at merging theory and practice by demonstrating how concepts from graph theory can be applied to various areas in computer science, and by extracting new graph theoretic problems from applications.